Development of an Enantioselective Route towards the Lycopodium Alkaloids: Total Synthesis of Lycopodine - Yang, Hua (2010)
Synthesis of a C(15)-desmethyl tricycle core of lycopodine has been accomplished. Key steps in the synthetic sequence include organocatalytic, intramolecular Michael addition of a keto sulfone and a tandem 1,3-sulfonyl shift / Mannich cyclization to construct the tricyclic core ring system. Synthetic work towards this natural product family led to the development of N-(p-dodecylphenylsulfonyl)-2-pyrrolidinecarboxamide – an organocatalyst which facilitiates enantioselective, intramolecular Michael additions. A detailed mechanistic discussion is provided for both the intramolecular Michael addition and the sulfone rearrangement. Finally, the application of these discoveries to the enantioselective total synthesis of alkaloid lycopodine is described.